2019
DOI: 10.1001/jamaneurol.2019.1632
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Fully Automated Plasma Assays as Screening Tests for Alzheimer Disease–Related β-Amyloid Status

Abstract: IMPORTANCE Accurate blood-based biomarkers for Alzheimer disease (AD) might improve the diagnostic accuracy in primary care, referrals to memory clinics, and screenings for AD trials. OBJECTIVE To examine the accuracy of plasma β-amyloid (Aβ) and tau measured using fully automated assays together with other blood-based biomarkers to detect cerebral Aβ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
355
3
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 340 publications
(388 citation statements)
references
References 51 publications
28
355
3
2
Order By: Relevance
“…We acknowledge that cross‐validation in external cohorts is essential. Of note, our results do not stand alone; multiple recent studies using highly sensitive immunoassays for blood‐based amyloid beta quantification showed capability to discriminate between amyloid‐positive and amyloid‐negative cognitively normal individuals, with or without subjective cognitive complaints, providing independent support for our findings. Moreover, in our article we not only investigated the association of plasma amyloid and CSF amyloid, but showed that low plasma amyloid levels are related to a higher risk of subsequent clinical disease progression to mild cognitive impairment or dementia.…”
supporting
confidence: 71%
“…We acknowledge that cross‐validation in external cohorts is essential. Of note, our results do not stand alone; multiple recent studies using highly sensitive immunoassays for blood‐based amyloid beta quantification showed capability to discriminate between amyloid‐positive and amyloid‐negative cognitively normal individuals, with or without subjective cognitive complaints, providing independent support for our findings. Moreover, in our article we not only investigated the association of plasma amyloid and CSF amyloid, but showed that low plasma amyloid levels are related to a higher risk of subsequent clinical disease progression to mild cognitive impairment or dementia.…”
supporting
confidence: 71%
“…Blood samples were collected at the same time as CSF samples and handled according to a structured pre‐analytical protocol (Palmqvist et al , ). Plasma Aβ42, Aβ40, and T‐tau concentrations were measured using the Elecsys ® immunoassays on a cobas e ® 601 analyzer (Palmqvist et al , ). NfL was analyzed as previously described (Hansson et al , ).…”
Section: Methodsmentioning
confidence: 99%
“…Recent advancements in proteomic assays have demonstrated the potential use of plasma Aβ to identify brain Aβ‐positive individuals with moderate‐to‐high accuracy [4–8]. The measurement of T‐tau in plasma has limited diagnostic value, albeit being slightly but significantly increased in patients with AD [9] but promising data are emerging on P‐tau [10].…”
Section: Introductionmentioning
confidence: 99%
“…Recent advancements in proteomic assays have demonstrated the potential use of plasma Ab to identify brain Abpositive individuals with moderate-to-high accuracy [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%